Tensions between the Prescriptive and Descriptive Ethics of Psychologists - Voskuijl, Olga (Journal of business ethics, 2007)
Ethical guidelines for psychologists are meant to stimulate and help psychologists to act appropriately with respect to clients, colleagues, and other individuals involved in their professional relations. This paper focuses on the similarity of codes of ethics of psychologists in European countries in general, and on specific ethical dilemmas in the area of work and organizations in particular. First, an overview is given of the development of ethical guidelines in Europe and the USA. Second, the results are presented of a survey by E-mail amongst members of the European Federation of Psychologists’ Associations (EFPA) to identify the differences and similarities between ethical guidelines of the affiliate members. Third, the potential dilemmas of stakeholders in work and organizational assessment are addressed. Finally, the results of a survey among Dutch selection psychologists are presented. The purpose of this study was to examine a possible tension between normative behavior and attitudes about normal behavior. It was concluded that ethical guidelines of European countries cover comparable (sub-)principles and that there are indications that individual psychologists agree with the written principles. In addition, suggestions for future research are given.